The giant African snail, Achatina fulica (Gastropoda: Achatinidae): Using bioclimatic models to identify South American areas susceptible to invasion - Vogler, Roberto Eugenio (2013)
Fil: Vogler, Roberto Eugenio. División Zoología Invertebrados. Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina